HUBUNGAN PENGETAHUN DENGAN KEPATUHAN PASIEN TUBERKULOSIS PARU DALAM PENGOBATAN DI PUSKESMAS PEMBANTU LIMAU SUNDAI BINJAI BARAT TAHUN 2016 - Leny Suarni (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Pulmonary tuberculosis is a common infectious disease and many cases are deadly. The most important thing that must be considered and carried out by patients with pulmonary tuberculosis is regularity in taking medicine, if this is not done then the treatment carried out previously becomes useless, because the pulmonary tuberculosis germs become immune, making it difficult to treat. This study uses a correlation study aimed to determine the relationship of knowledge with adherence to patients with pulmonary tuberculosis in treatment at the Sundai Limau Auxiliary Health Center. The population was all patients at the Sundai Maid Health Center, samples from the study used a total sampling of 20 people. Data collection using a questionnaire. Data analysis consisted of univariate and bivariate analysis. The results of the study showed that the level of knowledge in the good category was 12 people (60%), knowledge with sufficient categories and less for 4 people (20%). The majority of respondents had good adherence as many as 10 people (50%), compliance with enough categories as many as 6 people (30%), and compliance with less categories as many as 4 people (20%), and there was a relationship of knowledge with compliance with pulmonary tuberculosis patients in treatment at Limau Sundai Health Center (t count 2.502> t table 0.456). It is hoped that the Limau Sundai Health Center will increase the provision of information through counseling activities to the community, especially patients with pulmonary tuberculosis in order to increase the knowledge and compliance of patients in the treatment of pulmonary tuberculosis.Keywords: Knowledge, Compliance, Lung Tuberculosis